Dynamics of hole singlet-triplet qubits with large g-factor differences - Jirovec, D; Mutter, PM; Hofmann, A; Crippa, A; Rychetsky, M; Craig, DL; Kukucka, J; Martins, F; Ballabio, A; Ares, N; Chrastina, D; Isella, G; et al. (American Physical Society, 2022)
The spin-orbit interaction permits to control the state of a spin qubit via electric fields. For holes it is particularly strong, allowing for fast all electrical qubit manipulation, and yet an in-depth understanding of this interaction in hole systems is missing. Here we investigate, experimentally and theoretically, the effect of the cubic Rashba spin-orbit interaction on the mixing of the spin states by studying singlet-triplet oscillations in a planar Ge hole double quantum dot. Landau-Zener sweeps at different magnetic field directions allow us to disentangle the effects of the spin-orbit induced spin-flip term from those caused by strongly site-dependent and anisotropic quantum dot g tensors. Our work, therefore, provides new insights into the hole spin-orbit interaction, necessary for optimizing future qubit experiments.